The official estimates of poverty in Pakistan – What is wrong and why? – Illustrations using the Government of Pakistan’s Household Integrated Economic Survey 2010-11 - Malik, Sohail Jehangir; Nazli, Hina; Whitney, Edward (International Food Policy Research Institute, 2014)
This paper aims to clarify the confusion over estimates of poverty in Pakistan1. The paper highlights the root causes of the confusion in the existing literature, which are based on estimates from the “nationally representative” data collected by the Federal Bureau of Statistics Household Integrated Economic Surveys (HIES). The paper uses the latest available HIES 2010-11 to illustrate and clarify these issues.